A new species of Homonota (Reptilia: Squamata: Gekkota: Phyllodactylidae) endemic to the hills of Paraje Tres Cerros, Corrientes Province, Argentina - Cajade, Rodrigo; Etchepare, Eduardo Gabriel; Falcione, Camila; Barrasso, Diego Andrés; Alvarez, Blanca Beatriz (Zootaxa, 2013)
The genus Homonota comprises nine South American species of terrestrial and nocturnal lizards. Homonota lizards lack the femoral pores typical of other South American Phyllodactylidae, and their infradigital lamellas are not expanded. We here describe a new species, Homonota taragui sp. nov., exclusively found on a small group of three hills up to 179 meters above sea level in central eastern Corrientes Province, Argentina. The new species differs from other Homonota species by a combination of characters, including: a well-marked dorsal, reticulate, dark pattern contrasting with a lighter colored background; small, star-shaped chromatophores on the abdomen; the post-orbital region of the head covered by granular scales; the dorsal and anterior regions of the thighs covered by keeled scales interspersed with cycloid scales; and the internasal scale in contact with rostral scales. The conservation status of Homonota taragui sp. nov. may be vulnerable, due to its localized endemism with populations on three small hills surrounded by intense agricultural and livestock activity. Two endemic plant species are known from these hills, and this new lizard represents the first endemic animal species.